Enhanced solar-driven interfacial vapor generation of lignite-based aerogel via water and thermal dual management - Mei Xiong; Hong-Lei Yan; Zhan-Ku Li; Wei-Dong Zhang; Jing-Chong Yan; Zhi-Ping Lei; Zhao Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui (Journal of Environmental Chemical Engineering, 2026)

An eco-friendly and cost-effective method for leaching lithium from spent LiFePO4 batteries involves using wood vinegar as a leaching agent - Huynh Tri; Chia-Hung Su; Balaji Panchal; Chun-Chong Fu; Shao-Jung Wu; Horng-Yi Juan (Hydrometallurgy, 2026)

18β-Glycyrrhetinic acid ameliorates renal anemia via inactivating PHD2 and activating HIF-2α-EPO axis - Jiaxuan Li; Kai Han; Yuhan Fu; Chong Zhao; Shutao Yin; Hongbo Hu (Food Research International, 2026)

40Ar/39Ar geochronology, SrNd isotopes and melting conditions of the Dahongshan alkaline basalts: Constraints on mantle modification beneath the northern Yangtze Craton - Yue Song; Xuan-Ce Wang; Simon A. Wilde; Xiang-Zhong Li; Chong-Jin Pang; Si-Yu Hu; Yang Luo; Jia-Xu Tang; Si-Zhe Fu (Chemical Geology, 2026)

Molecular gatekeeping in sludge EPS: pH–thermal forcing reshapes biopolymer interactions and carbon release pathways - Ziqi Yang; Yu Hua; Yu Fu; Chong Chen; Yue Zhang; Xiaohu Dai (Water Research, 2026)

Developing a fusion algorithm based on UAV and mobile monitoring to quantify black carbon emissions from various types of planned straw residue burning - Jing Fu; Weiwei Chen; Chong Hui; Xue Yang; Lin Liang; Bowen Shi (Atmospheric Environment, 2026)

Numerical Investigation of Time-Dependent Deformation and Fracture Evolution in Flawed Sandstone - Teng-Fei Fu; Zhu-Guang Wang; Bi-Bi Qiao; Ya-Tao Li; Tao Ding; Chong-Feng Chen (Geotechnical and Geological Engineering, 2026)

Evapotranspiration-partitioned generalized complementary relationship model for heterogeneous vegetation - Chong Fu; Weilin Liu; Xiaoyu Song; Lanjun Li; Lu Xia; Jing Yuan (Journal of Hydrology, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

Wearable and breathable double-sided alginate/silk fibroin aerogel-nanofiber-based flexible sensor for personal thermal management and distinguishable multimodal sensing applications - Yu Fu; Peng Liu; Zhenshuai Wan; Ye Tian; Peng Wang; Chong Liu; Peng Sun; Shaoshuai Li; Dengjie Zhu; Caixia Ren (Chemical Engineering Journal, 2026)

Engineering catalytic sites in ZnIn2S4 via Mg doping: A S-to-In shift toward enhanced photocatalytic H2 evolution - Yan Wang; Yuqi Shi; Xin Chong; Chao Wang; Rong Fu; Chang Liu; Yuelan Zhang (Chemical Engineering Journal, 2026)

Electrical–parameter–optimized joule heating of a carbon medium for high–efficiency CO2–to–CO conversion - Zhishang Wang; Zunrong Sheng; Nan Jiang; Chong Li; Zhiguo Zhao; Yongqiang Fu; Wenzhu Wu; Jie Li (Chemical Engineering Journal, 2026)

Estimation of the monthly change in soil water storage in two watersheds of contrasting vegetation cover - Chong Fu; Xiaoyu Song; Huaiyou Li (CATENA, 2026)

Paleomagnetic constraints on the northernmost boundary of the southeastward extrusion in the southeastern Tibetan Plateau - Wanlong Xu; Maodu Yan; Chong Guan; Qiang Fu; Liang Yu; Bingshuai Li; Dawen Zhang; Miaomiao Shen; Zunbo Xu; Yuwei Zhang (Science China Earth Sciences, 2026)

Bidirectional electron transfer enabled by dual electric fields for efficient 4-nitrophenol removal on a bifunctional FeCoNiP/PCN heterojunction - Yan Wang; Chang Liu; Rong Fu; Chao Wang; Xin Chong; Yuqi Shi; Yuelan Zhang (Journal of Environmental Chemical Engineering, 2026)

Light absorption property, oxidative potential and chemical composition of organic carbon emitted from the combustion of representative coals in China - Hao Na; Shaojie Yang; Jianwei Zheng; Jingxuan Yang; Fu Li; Xiangli Nan; Wangjin Yang; Chong Han (Journal of Environmental Sciences, 2026)

Seasonal temperature rise influences nitrous oxide and methane accumulation in freshwater habitats via distinctive microbial processes - Teng-Fei Ma; Wen-Ke Liu; Chong-Yang Xing; Ya-Song Chen; Hui-Min Fu; Ji-Chun Bai; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Meng-Wen Peng (Environmental Pollution, 2026)

Ten questions concerning Large Language Models (LLMs) for building applications - Nan Ma; Rania Labib; Robert Amor; Adrian Chong; Cheng Fan; Kasimir Forth; Xiaoqin Fu; Stefan Fuchs; Tianzhen Hong; Nina Klimenkova; Jabeom Koo; Shundong Li; et al. (Building and Environment, 2026)

On-exosome-membrane DNA polymerization-powered magneto-electrochemical aptasensing for osteosarcoma - Guang-Xian Zhong; Huang-Feng Lin; Fei-Huan Fu; Jing-Wei Zhou; Chong-Yu Chen; Chao-Yang Wu; Jian-Ping Lin; Xiong-Wei Xu; Jian-Hua Lin; Jin-Yuan Chen (Analytica Chimica Acta, 2026)

Eliminating Microcystis aeruginosa and secondary pollutants via photo-Fenton process over Iron-MOF - Hong- Yu Chu; Zheng-Xing Liu; Jian-Feng Wang; Xuchun Qiu; Fu-Xue Wang; Shao-Long Chen; Hui-Min Yu; Fei Wang; Guang-Chi Liu; Ruo-Xuan Mei; Xin-Jie Li; Xiao-Hang Xu; et al. (Water Research, 2026)

Structure-optimized hollow carbon spheres from lignite for advanced lithium–sulfur batteries - Yao Huang; Long-Jun Zhang; Wei Wang; Zhan-Ku Li; Xu Liu; Hong-Lei Yan; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui; et al. (Fuel, 2026)

FeSe2 graphite intercalation compounds derived from spent graphite with spatial confinement effect enable high-performance sodium storage - Jiahao Yang; Chong Xu; Zizheng Zhou; Guang Ma; Shuang Liu; Dongyuan Zhang; Gong Cheng; Junjie Fu; Sai Che; Yan Jia; Yongfeng Li (Chemical Engineering Journal, 2026)

Beyond Plant Diversity: Plant Productivity Responses to Extreme Drought Are Linked to Arbuscular Mycorrhizal Fungal Diversity - Wei Fu; Qiang Yu; Haiyang Zhang; Chong Xu; Xingguo Han; Baodong Chen (Global Change Biology, 2026)
Plant and arbuscular mycorrhizal (AM) fungal diversity are both positively linked to ecosystem productivity across diverse ecosystems. However, given their high sensitivity to climate extremes such as extreme drought, the persistence and adaptability of these diversity‐productivity relationships under rapid climate changes remain poorly understood. To address this, we established a grassland experiment at two proximate sites with distinct natural plant and AM fungal communities, imposing two contrasting extreme drought regimes (intense and chronic), each exceeding a 20‐year recurrence interval based on site‐specific precipitation records. We show that AM fungal diversity consistently outperforms plant diversity in predicting plant aboveground/net primary productivity (ANPP/NPP), as well as compositional shifts in plant species productivity, despite pronounced drought sensitivity in both communities. Notably, enhanced drought resistance in plant productivity was primarily associated with the stability of AM fungal richness rather than plant richness, highlighting their mutual dependence under extreme drought. Structural equation modelling confirmed that AM fungal richness buffered drought effects on ANPP, NPP and plant richness, with stronger effects on ANPP and NPP than those of plant richness and soil properties. These results suggest that AM fungal diversity may play a greater role than plant diversity in buffering plant communities against climate extremes. While causality remains to be fully resolved, these findings shed light on the adaptive significance of this ancient symbiont in sustaining ecosystem functioning under rapid climate change.

Ni/Al-based additives for deep desulfurization of high-sulfur coal: Cooperative desulfurization and sulfur migration behavior - Zheng-Zhi Zhang; Zhan-Ku Li; Jing-Tao Yao; Mu-Xin Liu; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Cai Wang; Zhi-Ping Lei; Shi-Biao Ren; Heng-Fu Shui (Journal of Environmental Chemical Engineering, 2025)

High-performance and fast fiber-optic SPR gas sensor based on WO3/SnO2 nanocomposites films for room-temperature NH3 detection - Chong Li; Yan Wang; Jinqiao Hou; Huanming Wang; Jingting Luo; Chen Fu; Fujian Ren; Jikai Zhang; Huiling Ong; Chenze Lu; Hang Xiao; Xi Chen; et al. (Journal of Environmental Chemical Engineering, 2025)

BIM-to-BRICK: Using graph modeling for IoT/BMS and spatial semantic data interoperability within digital data models of buildings - Filippo Vittori; Chuan Fu Tan; Anna Laura Pisello; Adrian Chong; Cristina Piselli; Clayton Miller (Energy and Buildings, 2025)

Meiotic cytokinesis defects in cultured Arabidopsis flowers induce diploid microspores - Huiqi Fu; Yuting Chen; Xueying Cui; Huishan He; Jingru Wang; Chong Wang; Ziming Ren; Bing Liu (Plant Reproduction, 2025)

A comprehensive review of recent progress on the drought-flood abrupt alternation - Gengxi Zhang; Huimin Wang; Thian Yew Gan; Shuyu Zhang; Jin Zhao; Xiaoling Su; Xiaolei Fu; Lijie Shi; Pengcheng Xu; Miao Lu; Chong Wang (Journal of Hydrology, 2025)

Microfluidic device for high-throughput cancer drug screenings - Po-Hsun Chen; Lin-Yu Wang; Chia-Yuan Chang; Yuh-Shiuan Chien; Yu-Chia Su; Chi-Kuang Wang; Kuang-Chong Wu; Hsian-Jean Chin; Chien-Fu Chen (Chemical Engineering Journal, 2025)

Tailoring molecular structure of coal tar for monolithic phenolic aerogels to reduce enthalpy for solar desalination - Yu Han; Hong-Lei Yan; Zhan-Ku Li; Wei-Dong Zhang; Jing-Chong Yan; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui; Lun-Jing Yan (Journal of Environmental Chemical Engineering, 2025)

A review of municipal sewage sludge biological material applications in biofuel and environmental pollution control and future opportunities - Balaji Panchal; Chia-Hung Su; Chun-Chong Fu; Shao-Jung Wu; Horng-Yi Juan (Journal of Environmental Chemical Engineering, 2025)

Pre-carbonization facilitates closed pore formation in asphalt-derived hard carbon for high-plateau-capacity sodium storage - Chong Xu; Dongyuan Zhang; Guang Ma; Shuang Liu; Gong Cheng; Junjie Fu; Ye Wang; Runyi Xu; Chen Ling; Sai Che; Yongpeng Cui; Yongfeng Li (Chemical Engineering Journal, 2025)

Spatial distribution, phase partitioning, and ecological risk assessment of typical pesticides in Yangtze River Basin - Chengcheng Bu; Chong Chen; Xitong Fu; Weiwei Zhang; Ru Zhang; Yu Hua; Ruolan Jia; Yuefei Ruan; Kenneth Mei Yee Leung; Limin Ma (Journal of Hazardous Materials, 2025)

Selective detection of copper (II) dynamics in living cells and mice with diverse metabolic dysfunction-associated steatotic liver disease using a turn-on bioluminescent probe - Chong Hu; Xiaorui Shi; Jie Zhou; Zeping Yang; Zhenlong Wang; Liyu Huang; Chu Tang; Fu Wang (Journal of Hazardous Materials, 2025)

Z-scheme MIL-88A(Fe)/LaFeO3 heterostructured photocatalyst: Boosting photo-Fenton activity for enhanced organic pollutant detoxification - Ruo-Xuan Mei; Peng Wang; Fu-Xue Wang; Zi-Chen Zhang; Xiao-Hong Yi; Zi-Yu Jia; Ke-Xin Li; Chong-Chen Wang (Environmental Research, 2025)

A simple and efficient Agrobacterium rhizogenes-mediated CRISPR/Cas9 gene editing system in Lathyrus odoratus - Yafen Fu; Ximan He; Wenwen Wang; Zhou Chen; Zheng Hong; Bingzhen Du; Chong Wang; Hui Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

NO2-promoted heterogeneous photochemical oxidation of SO2 to sulfates on brown carbon - Hongxing Yang; Wangjin Yang; Shiwei Lai; Fu Li; Shaojie Yang; Chong Han (Environmental Pollution, 2025)

Climatic driving mechanisms of the propagation from meteorological drought to agricultural and ecological droughts - Chong Li; Yongshuo Fu; Qianzuo Zhao; Xuan Zhang; Ruiqiang Ding; Fanghua Hao; Guodong Yin (Journal of Environmental Management, 2025)

Planting date adjustment and varietal replacement can effectively adapt to climate warming in China southern rice area - Yixuan Wang; Shuo Li; Jiongchao Zhao; Chong Wang; Yupeng Feng; Mingyu Zhao; Xiaoyu Shi; Fu Chen; Qingquan Chu (Agricultural Systems, 2025)

Exosomes secreted from M2-polarized macrophages inhibit osteoclast differentiation via CYLD - Zi-yan Guo; Nan-nan Yin; Xiao-fei Li; Meng-meng Wang; Xiao-na Sui; Cai-di Jiang; Ming-hua Xu; Xiao-e Jia; Chong-jian Fu; Tie-lou Chen; Xin Liu (Tissue and Cell, 2025)

Impacts of sulfamethoxazole on heterotrophic nitrification-aerobic denitrification bacteria and its response strategies: Insights from physiology to proteomics - Teng-Fei Ma; Xiao-Yao Yu; Chong-Yang Xing; Hui-Min Fu; Hao-Yang Duan; You-Peng Chen (Journal of Environmental Management, 2025)

Physiological and proteomic insights into silver nanoparticle-induced stress responses and resistance mechanisms in aerobic denitrifying Enterobacter cloacae HNR - Teng-Fei Ma; Hong-Xi Ma; Chong-Yang Xing; Hui-Min Fu; Yu Shen; You-Peng Chen; Xiang-Yang Wei (Journal of Environmental Chemical Engineering, 2025)

Preparation of high-performance SiOx anode materials via dual interfacial reinforcement strategy - Ye Wang; Chong Xu; Junjie Fu; Sai Che; Guang Ma; Kaiyi Chen; Jiahao Yang; Shuang Liu; Gong Cheng; Dongyuan Zhang; Yunen Huang; Wenyue Gao; et al. (Chemical Engineering Journal, 2025)

A deep data fusion-based reconstruction of water index time series for intermittent rivers and ephemeral streams monitoring - Junyuan Fei; Xuan Zhang; Chong Li; Fanghua Hao; Yahui Guo; Yongshuo Fu (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Relationship between pyrolytic sulfur migration behavior and structural composition of high-sulfur fat coal - Zhan-Ku Li; Zheng-Zhi Zhang; Kai Zhang; Hong-Lei Yan; Jing-Chong Yan; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Shi-Gang Kang; Heng-Fu Shui (Fuel, 2025)

Mechanisms of hydraulic erosion control in different microrelief patterns of loess sloped farmland under continuous rainfall - Xinkai Zhao; Xiaoyu Song; Danyang Wang; Lanjun Li; Pengfei Meng; Chong Fu; Long Wang; Wanyin Wei; Yu Liu; Huaiyou Li (CATENA, 2025)

New Paleomagnetic results from Late Triassic limestone of the Eastern Qiangtang Terrane: Implications for the closure of the Paleo-Jinshajiang Ocean - Liang Yu; Maodu Yan; Mathew Domeier; Bingshuai Li; Miaomiao Shen; Chong Guan; Qiang Fu; Wanlong Xu; Zunbo Xu; Zhichao Niu; Dawen Zhang; Liye Yang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Six element high-entropy Prussian blue analogue cathode enabling high cycle stability for sodium-ion batteries - Zhe Qian; Rui-Jie Luo; Cui Ma; Chong-Yu Du; Jie Zeng; Xuan Xu; Zhe Mei; Zi-Ting Zhou; Zheng-Wen Fu; Yong-Ning Zhou (Chemical Engineering Journal, 2024)

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

Reactive oxygen species play key roles in the nitrite formation by the inorganic nitrate photolysis in the presence of urban water-soluble organic carbon - Wangjin Yang; Zhifu Xia; Jianwei Zheng; Fu Li; Xiangli Nan; Tao Du; Chong Han (Science of The Total Environment, 2024)

Failure envelope for offshore rigid piles under combined horizontal-moment loading in clay with linearly increasing undrained shear strength - Xiaodong Shao; Chong Jiang; Yong Fu; Juncheng Yao; Li Pang (Ocean Engineering, 2024)

Ferrocenedicarboxylate modified Bi-MOF for water decontamination via different advanced oxidation processes: Multifunction, mechanisms and biotoxicity test - Ya Gao; Fei Wang; Jie Tang; Chong-Chen Wang; Xiao-Hong Yi; Yuwei Wei; Guangchi Liu; Peng Wang; Huifen Fu; Chen Zhao; Xuchun Qiu; Shouliang Yi (Chemical Engineering Journal, 2024)

Influence of suspended particles and dissolved organic matters on virus enrichment in reclaimed water by two-step tangential flow ultrafiltration: Phenomena and mechanisms - Zhen Wang; Chong-Miao Zhang; Yong-Fu Li (Journal of Hazardous Materials, 2024)

Floating MIL-88A(Fe)@expanded perlites catalyst for continuous photo-Fenton degradation toward tetracyclines under artificial light and real solar light - Guang-Chi Liu; Xiao-Hong Yi; Hong-Yu Chu; Chong-Chen Wang; Ya Gao; Fei Wang; Fu-Xue Wang; Peng Wang; Jian-Feng Wang (Journal of Hazardous Materials, 2024)

Remagnetization of magnetite-bearing rocks in the Eastern Qiangtang Terrane, Tibetan Plateau (China): Mechanism and diagnosis - Qiang Fu; Maodu Yan; Mark J. Dekkers; Chong Guan; Liang Yu; Wanlong Xu; Zunbo Xu; Miaomiao Shen; Bingshuai Li (Physics of the Earth and Planetary Interiors, 2024)

Enhanced mineralization capacity for photocatalytic toluene degradation over Ag3PO4/TiO2: the critical role of oxygen vacancy - Chaoting Jia; Huifen Fu; Zhihua Wang; Chen Zhao; Chong-Chen Wang (Journal of Environmental Chemical Engineering, 2024)

Vertically aligned and conformal BN-coated carbon fiber to achieve enhanced thermal conductivity and electrical insulation of a thermal interface material - Min Huang; Zhiqian Wang; Nizao Kong; Biao Li; Chong Ye; Kun Jia; Liqin Fu; Yexin Tian; Donghong Wang; Fei Han (Chemical Engineering Journal, 2024)

Robustness of design flood estimates under nonstationary conditions: parameter sensitivity perspective - Bin Xiong; Shuchen Zheng; Qiumei Ma; Chun Fu; Tianfu Wen; Zhongzheng He; Lingqi Li; Chong-Yu Xu (Stochastic Environmental Research and Risk Assessment, 2024)
The changing frequency of flooding in global watersheds, driven by various human and natural factors like land use/cover changes and global warming, necessitates innovative approaches in flood frequency analysis and risk assessment. Nonetheless, the reliability of nonstationary frequency analysis models remains a concern given challenges in accurately measuring the uncertainty introduced by these methods and the impact on design flood values. In this study, deviation-based differential sensitivity indices, including single-parameter (SDDSI) and entire-parameter (EDDSI) measures were developed to assess the influence of parameter uncertainty in nonstationary models using Bayesian statistics and "equivalent reliability" nonstationary design. The Weihe River, the largest tributary of the Yellow River which is experiencing both climate change and heavy impact of human activities, is chosen to be the study area to investigate the impact of precipitation change and land use change on nonstationary flood frequency. Results show that in the One-At-A-Time (OAT) sensitivity analysis under a small uncertainty scenario (SUS) for parameter inputs, the shape parameter stands out as the most influential factor (SDDSI_SUS = 0.347) affecting the 100-year design flood in the Stationary Generalized Extreme Value (SGEV) model. For the Non-Stationary GEV (NGEV) models, the influence of this parameter is less pronounced, with SDDSI_SUS values of 0.095 and 0.093 for the SSP126 and SSP585 scenarios, respectively. Instead, attention turns to the regression coefficient of the grassland area, associated with the GEV scale parameter. In global sensitivity analysis under the posterior uncertainty scenario (PUS) for parameter inputs, the EDDSI_PUS values for SGEV, NGEV_SSP126, and NGEV_SSP585 models were 0.52, 1.41, and 1.30, respectively, inferring heightened sensitivity of NGEV models to perturbations from entire parameters. It is anticipated that incorporating additional evidence, such as historical flood data, is essential for accurate nonstationary hydrological design to mitigating the influence of parameter uncertainty. The sensitivity indices in this study provide significant insights for assessing the robustness of nonstationary hydrological design in flood risk management and applications.

Nanoplastic toxicity induces metabolic shifts in Populus × euramericana cv. '74/76' revealed by multi-omics analysis - Liren Xu; Chong Liu; Yachao Ren; Yinran Huang; Yichao Liu; Shuxiang Feng; Xinyu Zhong; Donglin Fu; Xiaohong Zhou; Jinmao Wang; Yujun Liu; Minsheng Yang (Journal of Hazardous Materials, 2024)

50° Post-Eocene clockwise rotation of Mangkang and its implications for the oroclinal bending of the southeastern Tibetan Plateau - Wanlong Xu; Maodu Yan; Douwe J.J. van Hinsbergen; Bingshuai Li; Chong Guan; Qiang Fu; Liang Yu; Zunbo Xu; Dawen Zhang; Miaomiao Shen; Zhantao Feng; Zhichao Niu; et al. (Gondwana Research, 2024)

Prussian blue analogue nanospheres immobilized on self-floating biochar for micropollutant degradation via photo-Fenton process - Fu-Xue Wang; Zi-Wei Zhang; Zi-Chen Zhang; Ke-Xin Li; Ya Li; Hong-Yu Chu; Chong-Chen Wang; Jian-Feng Wang; Long Chen; Wen Liu; Hailong Wang; Peng Wang (Chemical Engineering Journal, 2024)

The spatial-temporal evolution and driving mechanism of Urban resilience in the Yellow River Basin cities - Haiyang Li; Ying Wang; Hongwei Zhang; Ruimin Yin; Chong Liu; Zhaojun Wang; Fen Fu; Jiaqi Zhao (Journal of Cleaner Production, 2024)

Photocatalytic depolymerization of lignin to produce high value-added chemicals by carbon quantum dots modified WO3 nanosheets - Zhijie Jiang; Xutang Liu; Wei Zhao; Fei Wang; Mingyu Cui; Linyang Dong; Chong Liang; Dingkai Wang; Shuiyuan Fu (Journal of Environmental Chemical Engineering, 2024)

Self-floating, monolithic, and aligned phenolic carbon aerogels from coal tar for solar-driven evaporation - Hong-Lei Yan; Jin-Yuan Cheng; Zhan-Ku Li; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui (Fuel, 2024)

Zwitterionic peptide pendant as a homing agent to achieve lymphatic targeting antigen-specific immunotherapy of allergenic protein - Huan Li; Dong Yuan; Chong Wang; Yifan Wang; Jiachao Zhang; Zhenxing Li; Zhongshan Gao; Linglin Fu (Chemical Engineering Journal, 2024)

Observing eddy dye patches induced by shear instabilities in the surf zone on a plane beach - Chunping Ren; Nannan Fu; Chong Yu; Yuchuan Bai; Kezhao Fang (Acta Oceanologica Sinica, 2024)

Preservation effects and antimicrobial mechanism of ultrasound assisted rosmarinic acid treatment on large yellow croaker during cold storage - Yunqing Chong; Jingjing Fu; Tingting Chai; Yangna Huang; Danli Jin; Junlong Mao; Yuewen Chen (Food Bioscience, 2024)

Inverse magnetic fabric of remagnetized limestones in the Zaduo area, Eastern Qiangtang Terrane: Implications for oroclinal bending in the Eastern Himalayan Syntaxis - Qiang Fu; Maodu Yan; Mark J. Dekkers; Bingshuai Li; Chong Guan; Liang Yu; Wanlong Xu; Miaomiao Shen; Zunbo Xu (Tectonophysics, 2024)

Two-level collaborative demand-side management for regional distributed energy system considering carbon emission quotas - Jiaqi Yuan; Wenjie Gang; Fu Xiao; Chong Zhang; Ying Zhang (Journal of Cleaner Production, 2024)

Synthetic polymer fracturing fluid weighted by sodium formate enables fracture stimulations in Ultra-High pressure and High-Temperature reservoir - Xiaojiang Yang; An Chen; Jincheng Mao; Chong Zhang; Juanjuan Wang; Meitao Fu; Hu Zhang; Junjian Wang; Xianshi Song; Yang Zhang; Chong Lin (Fuel, 2023)

Numerical simulation of flow instability induced by a fixed cylinder placed near a plane wall in oscillating flow - Zi-Fang Li; Jiang-Hua Li; Jian-Zhao Wu; Kai-Leong Chong; Bo-Fu Wang; Quan Zhou; Yu-Lu Liu (Ocean Engineering, 2023)

Amino acids as in-situ electron donors drive medium chain fatty acids production from sludge acidogenic fermentation liquid by electro-fermentation enhancement - Ping Wu; Peng Ding; Qi-hao Cao; Chao Zhang; Bo Fu; Hong-bo Liu; Chong-jun Chen; He Liu (Chemical Engineering Journal, 2023)

An integrated machine learning framework with uncertainty quantification for three-dimensional lithological modeling from multi-source geophysical data and drilling data - Zhiqiang Zhang; Gongwen Wang; Emmanuel John M. Carranza; Chong Liu; Junjian Li; Chao Fu; Xinxing Liu; Chao Chen; Junjie Fan; Yulong Dong (Engineering Geology, 2023)

Pan-cancer evidence of prognosis, immune infiltration, and immunotherapy efficacy for annexin family using multi-omics data - Chong Shen; Siyang Zhang; Zhe Zhang; Shaobo Yang; Yu Zhang; Yuda Lin; Chong Fu; Zhi Li; Zhouliang Wu; Zejin Wang; Zhuolun Li; Jian Guo; et al. (Functional & Integrative Genomics, 2023)

A yolk-shell Pd decorated Au@CeO2 with Schottky junction for long-lived charge separation and bandgap optimization to enhance sonodynamic therapy - Weiwei Sheng; Xiunan Wu; Mengying Fu; Cheng Chen; Zetai Bai; Mengyuan Xing; Chun Zhang; Lijuan Chong; Jingjing Li; Fenglei Gao (Chemical Engineering Journal, 2023)

Mesomechanical characteristics of rock failure under variable amplitude cyclic loading by DEM - Ze-han Liu; Jin Yu; Chong-hong Ren; De-fu Zhu; Xiao-qin Chen (Bulletin of Engineering Geology and the Environment, 2023)

Effects of intra-year precipitation variability on shrub community productivity depend on the annual total rainfall - Ming-Han Yu; Ying-Ying He; Fu-Chong Zhang; Guo-dong Ding; Chun-Yuan Wang (Plant and Soil, 2023)

Enhanced photo-Fenton activity and stability for sulfamethoxazole degradation by FeS2@TiO2 heterojunction derived from MIL-125 - Aofei Du; Huifen Fu; Peng Wang; Chong-Chen Wang (Chemosphere, 2023)

Fabrication strategies of metal–organic frameworks derivatives for catalytic aqueous pollutants elimination - Fei Wang; Ya Gao; Shan-Shan Liu; Xiao-Hong Yi; Chong-Chen Wang; Huifen Fu (Chemical Engineering Journal, 2023)

Occurrence and ecological risk assessment of 16 phthalates in surface water of the mainstream of the Yangtze River, China - Jia-Nan Ren; Ning-Zheng Zhu; Xiang-Zhou Meng; Chong-Jing Gao; Kai Li; Li-Min Jin; Ting-Ting Shang; Fang-Ting Ai; Ming-Hong Cai; Jian-Fu Zhao (Environmental Science and Pollution Research, 2023)

A review and reflection on open datasets of city-level building energy use and their applications - Xiaoyu Jin; Chong Zhang; Fu Xiao; Ao Li; Clayton Miller (Energy and Buildings, 2023)

Repetitive transcranial magnetic stimulation enhances the neuronal excitability of mice by regulating dynamic characteristics of Granule cells’ Ion channels - Haijun Zhu; Xiaonan Yin; Huilan Yang; Rui Fu; Wentao Hou; Chong Ding; Guizhi Xu (Cognitive Neurodynamics, 2023)

Integrated effects of residual plastic films on soil-rhizosphere microbe-plant ecosystem - Fei Fu; Bibo Long; Qian Huang; Juanjuan Li; Weijun Zhou; Chong Yang (Journal of Hazardous Materials, 2023)

Selective oxidation of aqueous organic pollutants over MOFs-based catalysts: A mini review - Fu-Xue Wang; Zi-Chen Zhang; Chong-Chen Wang (Chemical Engineering Journal, 2023)

Peroxymonosulfate activation for effective atrazine degradation over a 3D cobalt-MOF: Performance and mechanism - Ya Li; Fei Wang; Xueying Ren; Peng Wang; Fu-Xue Wang; Hong-Yu Chu; Shijie Gao; Chong-Chen Wang (Journal of Environmental Chemical Engineering, 2023)

A multi-agent system based coordinated multi-objective optimal load scheduling strategy using marginal emission factors for building cluster demand response - Hanbei Zhang; Fu Xiao; Chong Zhang; Rongling Li (Energy and Buildings, 2023)

Sustainable water and nitrogen optimization to adapt to different temperature variations and rainfall patterns for a trade-off between winter wheat yield and N2O emissions - Chong Wang; Zhiming Qi; Jiongchao Zhao; Zhenzhen Gao; Jie Zhao; Fu Chen; Qingquan Chu (Science of The Total Environment, 2023)

A six-year record of greenhouse gas emissions in different growth stages of summer maize influenced by irrigation and nitrogen management - Zhenzhen Gao; Jiongchao Zhao; Chong Wang; Yixuan Wang; Mengfei Shang; Zhipeng Zhang; Fu Chen; Qingquan Chu (Field Crops Research, 2023)

Near-infrared I/II emission and absorption carbon dots via constructing localized excited/charge transfer state for multiphoton imaging and photothermal therapy - Wen-Bo Zhao; Dan-Dan Chen; Kai-Kai Liu; Yong Wang; Rui Zhou; Shi-Yu Song; Fu-Kui Li; Lai-Zhi Sui; Qing Lou; Lin Hou; Chong-Xin Shan (Chemical Engineering Journal, 2023)

Evolution stage, spatial and temporal variabilities of granite landforms in the Mount Wugongshan in Jiangxi Province of South China - Le Chai; Cun-di Zhong; Fu-sheng Guo; Xin-shu Huang; Dao-ying Wang; Chong-jian Shao; Liu-qin Chen (Journal of Mountain Science, 2022)

Wheat genomic study for genetic improvement of traits in China - Jun Xiao; Bao Liu; Yingyin Yao; Zifeng Guo; Haiyan Jia; Lingrang Kong; Aimin Zhang; Wujun Ma; Zhongfu Ni; Shengbao Xu; Fei Lu; Yuannian Jiao; et al. (Science China Life Sciences, 2022)

Risk control effectiveness of phosphorus-containing passivators on Cd-contaminated agricultural soils to be strictly controlled - Chunfa Wu; JinLu Zhang; Yu Zhang; Shaopo Deng; Chong Wang; Zhaocong Fu (Journal of Soils and Sediments, 2022)

Automatic skin lesion classification using a new densely connected convolutional network with an SF module - Pufang Shan; Chong Fu; Liming Dai; Tihui Jia; Ming Tie; Jun Liu (Medical & Biological Engineering & Computing, 2022)

IL-38, a potential therapeutic agent for lupus, inhibits lupus progression - Wang-Dong Xu; Lin-Chong Su; Lu Fu; You-Yu Lan; Xiao-Yan Liu; Qi Huang; Qian Wu; Jie Zhou; An-Fang Huang (Inflammation Research, 2022)

Effect of different washing solutions on soil enzyme activity and microbial community in agricultural soil severely contaminated with cadmium - Yu Zhang; Chunfa Wu; Shaopo Deng; Jinlu Zhang; Jinyu Hou; Chong Wang; Zhaocong Fu (Environmental Science and Pollution Research, 2022)

Reservoir Characterization Using Multi-component Seismic Data in a Novel Hybrid Model Based on Clustering and Deep Neural Network - Jiuqiang Yang; Niantian Lin; Kai Zhang; Chong Zhang; Chao Fu; Gaopeng Tian; Cuiyu Song (Natural Resources Research, 2021)

Degraded polysaccharides from Porphyra haitanensis: purification, physico-chemical properties, antioxidant and immunomodulatory activities - Yun-Feng Huo; Yin-Ting Li; Wei Xia; Chong Wang; Yuan-Yuan Xie; Yan-Bo Wang; Tao Zhou; Ling-Lin Fu (Glycoconjugate Journal, 2021)

Mercury horizontal spatial distribution in paddy field and accumulation of mercury in rice as well as their influencing factors in a typical mining area of Tongren City, Guizhou, China - Jingjing Du; Fang Liu; Ling Zhao; Chong Liu; Zhaocong Fu; Ying Teng (Journal of Environmental Health Science and Engineering, 2021)

Landslides triggered by the 6 September 2018 Mw 6.6 Hokkaido, Japan: an updated inventory and retrospective hazard assessment - Yulong Cui; Pengpeng Bao; Chong Xu; Siyuan Ma; Jun Zheng; Gui Fu (Earth Science Informatics, 2021)

Porous Cd0.5Zn0.5S nanocages derived from ZIF-8: boosted photocatalytic performances under LED-visible light - Lin Wu; Huifen Fu; Qi Wei; Qian Zhao; Peng Wang; Chong-Chen Wang (Environmental Science and Pollution Research, 2021)

A big landslide on the Jinsha River, Tibet, China: geometric characteristics, causes, and future stability - Yulong Cui; Pengpeng Bao; Chong Xu; Gui Fu; Qisong Jiao; Yi Luo; Lingling Shen; Xiwei Xu; Fenglin Liu; Yuejun Lyu; Xiuhong Hu; Tao Li; et al. (Natural Hazards, 2020)

New gravimetric-only and hybrid geoid models of Taiwan for height modernisation, cross-island datum connection and airborne LiDAR mapping - Cheinway Hwang; Hung-Jui Hsu; W. E. Featherstone; Ching-Chung Cheng; Ming Yang; Wenhsuan Huang; Chong-You Wang; Jiu-Fu Huang; Kwo-Hwa Chen; Chi-Hsun Huang; Hechin Chen; Wen-Yi Su (Journal of Geodesy, 2020)

Spatio-temporal variations of vegetation carbon use efficiency and potential driving meteorological factors in the Yangtze River Basin - Xu-chun Ye; Fu-hong Liu; Zeng-xin Zhang; Chong-yu Xu; Jia Liu (Journal of Mountain Science, 2020)

Transferability of a Conceptual Hydrological Model across Different Temporal Scales and Basin Sizes - Sheng Sheng; Hua Chen; Fu-Qiang Guo; Jie Chen; Chong-Yu Xu; Sheng-lian Guo (Water Resources Management, 2020)

Transcriptional profiling of underground interaction of two contrasting sunflower cultivars with the root parasitic weed Orobanche cumana - Chong Yang; Fei Fu; Na Zhang; Jiansu Wang; Luyang Hu; Faisal Islam; Quanjiang Bai; Xiaopeng Yun; Weijun Zhou (Plant and Soil, 2020)

Small-scale catastrophic landslides in loess areas of China: an example of the March 15, 2019, Zaoling landslide in Shanxi Province - Yulong Cui; Chong Xu; Shiyang Xu; Shaofeng Chai; Gui Fu; Pengpeng Bao (Landslides, 2020)

An anthropogenic landslide dammed the Songmai River, a tributary of the Jinsha River in Southwestern China - Chong Xu; Yulong Cui; Xiwei Xu; Pengpeng Bao; Gui Fu; Wenliang Jiang (Natural Hazards, 2019)

Discovery of 3-(thiophen/thiazole-2-ylthio)pyridine derivatives as multitarget anticancer agents - Jiankang Zhang; Jianjun Xi; Ruoyu He; Rangxiao Zhuang; Limin Kong; Liping Fu; Yanmei Zhao; Chong Zhang; Linghui Zeng; Jingyi Lu; Rujia Tao; Zhengmengtong Liu; et al. (Medicinal Chemistry Research, 2019)

Age and nature of the Jurassic–Early Cretaceous mafic and ultramafic rocks from the Yilashan area, Bangong–Nujiang suture zone, central Tibet: implications for petrogenesis and tectonic Evolution - Yun Zhong; Xi-Chong Hu; Wei-Liang Liu; Bin Xia; Xiao Zhang; Wei Huang; Yuan-Bin Fu; Yu-Guang Wang (International Geology Review, 2018)

Ancylomarina psychrotolerans sp. nov., isolated from sediments of Fildes Peninsula and emended the description of genus Ancylomarina - Chao Jia; Hong-chang Cui; Yan-qiong Han; Tian-yu Fu; Rui Du; Xiao-lei Wang; Xiao-chong Shi; Xiao-Hua Zhang (Antonie van Leeuwenhoek, 2018)

Seafood allergen-induced hypersensitivity at the microbiota-mucosal site: Implications for prospective probiotic use in allergic response regulation - Linglin Fu; Chong Wang; Yanbo Wang (Critical Reviews in Food Science and Nutrition, 2018)

Transferability of Conceptual Hydrological Models Across Temporal Resolutions: Approach and Application - Meng-Xuan Jie; Hua Chen; Chong-Yu Xu; Qiang Zeng; Jie Chen; Jong-Suk Kim; Sheng-lian Guo; Fu-Qiang Guo (Water Resources Management, 2018)

Global changes of 5-hydroxymethylcytosine and 5-methylcytosine from normal to tumor tissues are associated with carcinogenesis and prognosis in colorectal cancer - Yi-ping Tian; Ai-fen Lin; Mei-fu Gan; Hao Wang; Dan Yu; Chong Lai; Dan-dan Zhang; Yi-min Zhu; Mao-de Lai (Journal of Zhejiang University-SCIENCE B, 2017)

Oroxylin A inhibits H 2 O 2 -induced oxidative stress in PC12 cells - Qinghe Han; Haiyu Wang; Chong Xiao; Ben-Dong Fu; Chong-Tao Du (Natural Product Research, 2017)

bFGF Protects Against Blood-Brain Barrier Damage Through Junction Protein Regulation via PI3K-Akt-Rac1 Pathway Following Traumatic Brain Injury - Zhou-Guang Wang; Yi Cheng; Xi-Chong Yu; Li-Bing Ye; Qing-Hai Xia; Noah R. Johnson; Xiaojie Wei; Da-Qing Chen; Guodong Cao; Xiao-Bing Fu; Xiao-Kun Li; Hong-Yu Zhang; et al. (Molecular Neurobiology, 2016)

Impact of Common Variations in PLD3 on Neuroimaging Phenotypes in Non-demented Elders - Chong Wang; Hui-Fu Wang; Meng-Shan Tan; Ying Liu; Teng Jiang; Dao-Qiang Zhang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2016)

Application of the non-seismic geophysical method in the deep geological structure study of Benxi-Huanren area - Chong Peng; Lin-Fu Xue; Zheng-Hong Liu; Hai-Yan Liu (Arabian Journal of Geosciences, 2016)

Different Responses of an Invasive Clonal Plant Wedelia trilobata and its Native Congener to Gibberellin: Implications for Biological Invasion - Zhi-Cong Dai; Wei Fu; Shan-Shan Qi; De-Li Zhai; Si-Chong Chen; Ling-Yun Wan; Ping Huang; Dao-Lin Du (Journal of Chemical Ecology, 2016)

Ultrasonic extraction of anthocyanin from Clitoria ternatea flowers using response surface methodology - Fui Chin Chong; Xian Fu Gwee (Natural Product Research, 2015)

Combination of intratypic and intertypic recombinant events in EV71: a novel evidence for the “triple-recombinant” strains of genotype A viruses in Mainland China from 2008 to 2010 - Yongjuan Liu; Fengfeng Zhang; Chong Fu; Suying Wu; Xiong Chen; Yingying Shi; Bingfei Zhou; Lianglu Zhang; Yingying Zhang; Song Han; Jun Yin; Biwen Peng; et al. (Virus Genes, 2015)

Substrate specificity and biochemical characterization of an adenylation domain from an obligate marine actinomycete - Xiao Shu; Yanling Ma; Chong Lu; Ming Lei; Yanli Liu; Ke Liu; Guomei Xiong; Sisi Xia; Zhijuan Zhao; Wenkai Luo; Qiao Fu; Chao Qi (Biotechnology Letters, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Indole-3-acetic acid reverses the harpin-induced hypersensitive response and alters the expression of hypersensitive-response-related genes in tobacco - Jie Song; Xiao-chong Gong; Wei-guo Miao; Fu-cong Zheng; Cong-feng Song; Ming-hua Wang (Biotechnology Letters, 2014)

A novel finding for enterovirus virulence from the capsid protein VP1 of EV71 circulating in mainland China - Yongjuan Liu; Chong Fu; Suying Wu; Xiong Chen; Yingying Shi; Bingfei Zhou; Lianglu Zhang; Fengfeng Zhang; Zhihao Wang; Yingying Zhang; Chengpeng Fan; Song Han; et al. (Virus Genes, 2014)

Is there a role of TNFR1 in acute lung injury cases associated with extracorporeal circulation? - Yu Zhao; Chong-wei Zhang; Wen-jing Zhou; Jiao Chen; Nan-fu Luo; Li-na Gong; Lei Du; Jing Zhou (Journal of Zhejiang University-SCIENCE B, 2014)

Expression of MyHC genes, composition of muscle fiber type and their association with intramuscular fat, tenderness in skeletal muscle of Simmental hybrids - Ming Zhang; Yu-liang Liu; Chong-yun Fu; Jie Wang; Shi-yi Chen; Jia Yao; Song-jia Lai (Molecular Biology Reports, 2014)

Identification of a novel frameshift mutation in PITX2 gene in a Chinese family with Axenfeld-Rieger syndrome - Hou-Fa Yin; Xiao-Yun Fang; Chong-Fei Jin; Jin-Fu Yin; Jin-Yu Li; Su-Juan Zhao; Qi Miao; Feng-Wei Song (Journal of Zhejiang University-SCIENCE B, 2014)

High-performance liquid chromatography with fluorescence detection for the determination of nitrofuran metabolites in pork muscle - Liang-Quan Sheng; Ming-Ming Chen; Shui-Sheng Chen; Na-Na Du; Zhao-Di Liu; Chong-Fu Song; Rui Qiao (Food Additives & Contaminants: Part A, 2013)

Ventral medial prefrontal functional connectivity and emotion regulation in chronic schizophrenia: A pilot study - Feng-Mei Fan; Shu-Ping Tan; Fu-De Yang; Yun-Long Tan; Yan-Li Zhao; Nan Chen; Bin-Bin Li; Chong-Sheng Song; Yun-Hui Wang; Zhen Jin; Dong-Feng Zhou; Michael P. Milham; et al. (Neuroscience Bulletin, 2013)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

A value chain approach to crisis response system: the case of Qingdao - Jian Hua Li; Zheng Ping Zhang; Rui Huan Jing; Chong Fu Huang (Stochastic Environmental Research and Risk Assessment, 2009)

Purification of High-quality Plastid DNA from the Brown Alga Laminaria japonica Sporophytes - Wandong Fu; Jianting Yao; Xiuliang Wang; Fuli Liu; Zhuo Chong; Delin Duan (Plant Molecular Biology Reporter, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Microsatellite variation in Avena sterilis oat germplasm - Yong-Bi Fu; James Chong; Tom Fetch; Ming-Li Wang (Theoretical and Applied Genetics, 2007)

FPF1 transgene leads to altered flowering time and root development in rice - Ming-Li Xu; Jia-Fu Jiang; Lei Ge; Yun-Yuan Xu; Hui Chen; Yuan Zhao; Yu-Rong Bi; Jiang-Qi Wen; Kang Chong (Plant Cell Reports, 2005)

Two genes encoding protein phosphatase 2A catalytic subunits are differentially expressed in rice - Richard Man Kit Yu; Yan Zhou; Zeng-Fu Xu; Mee-Len Chye; Richard Yuen Chong Kong (Plant Molecular Biology, 2003)